2017
DOI: 10.1111/1556-4029.13512
|View full text |Cite
|
Sign up to set email alerts
|

Provenance Establishment of Stingless Bee Honey Using Multi‐element Analysis in Combination with Chemometrics Techniques

Abstract: As consumption of stingless bee honey has been gaining popularity in many countries including Malaysia, ability to identify accurately its geographical origin proves pertinent for investigating fraudulent activities for consumer protection. Because a chemical signature can be location-specific, multi-element distribution patterns may prove useful for provenancing such product. Using the inductively coupledplasma optical emission spectrometer as well as principal component analysis (PCA) and linear discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…To date, no comprehensive study in Malaysia has been conducted to establish provenance of bee honeys according to their marker compounds especially from stingless bee species. To the best of our knowledge, only a study by Shadan et al [44] had documented the provenance establishment of stingless bee honey using multi-element analysis combined with chemometric techniques. Thus, our on-going study will further investigate the geographical origin of stingless bee honey samples specifically from Heterotrigona itama species collected from the four regions of Peninsular Malaysia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no comprehensive study in Malaysia has been conducted to establish provenance of bee honeys according to their marker compounds especially from stingless bee species. To the best of our knowledge, only a study by Shadan et al [44] had documented the provenance establishment of stingless bee honey using multi-element analysis combined with chemometric techniques. Thus, our on-going study will further investigate the geographical origin of stingless bee honey samples specifically from Heterotrigona itama species collected from the four regions of Peninsular Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in Malaysia by Shadan et al [44] exhibited the provenance of stingless bee honey collected from four different geographical regions of Johor, Malaysia (North, South, East and West) represented by five districts namely Segamat, Johor Bahru, Muar, Batu Pahat and Kota Tinggi. The collection period was during less rainy season in May, June and July.…”
Section: Fourier Transform-raman Spectroscopymentioning
confidence: 99%
“…Studies have shown that stingless bee honey (SBH) contains antimicrobial activity against bacteria, yeast, and fungal strains [ 2 ]. Further, SBH is considered to be a premium product with a market value that may reach up to $100/kg, which is approximately twice the price of the honey of the Apis bee, which ranges from $20 to $40/kg [ 3 ]. In Malaysia, the SBH industry is expanding due to its potential and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Chemometrics, as a method of data analysis, can objectively reflect the subtle differences among substances by establishing reasonable mathematical models [12, 13, 14, 15]. Hence, it is believed that the combination of infrared spectroscopy and chemometrics can be used to accurately distinguish and identify physical evidence.…”
Section: Introductionmentioning
confidence: 99%